Persistence of Severe Pulmonary Hypertension After Transcatheter Aortic Valve Replacement: Incidence and Prognostic Impact. (June 2016) - Testa, Luca; Latib, Azeem; De Marco, Federico; De Carlo, Marco; Fiorina, Claudia; Montone, Rocco; Agnifili, Mauro; Barbanti, Marco; Petronio, Anna Sonia; Biondi Zoccai, Giuseppe; Ettori, Federica; Klugmann, Silvio; et al.
Abstract : Background—: Severe pulmonary hypertension (PH) is considered to negatively affect the outcome after transcatheter aortic valve replacement. However, a clear understanding of the pattern, evolution, and clinical impact of different grades of PH in this setting is lacking. Methods and Results—: A total of 990 consecutive patients were enrolled in 6 high-volume centers and analyzed as follows: group 1, systolic pulmonary artery pressure (sPAP) <40 mm Hg (346 patients; 35%); group 2, sPAP 40 to 60 mm Hg (426 patients; 43%); and group 3, sPAP >60 mm Hg (218 patients; 22%). At 1 month, mortality rate did not differ across the groups. When compared with groups 1 and 2, patients in group 3 had a higher-rate of New York Heart Association 3 to 4 (26% versus 12% and 10%), and a higher-rate of hospitalization for heart failure (7% versus 3% and 3%). At 1 year, when compared with patients in group 1, patients in group 2 and 3 had both a higher overall mortality (hazard ratio [HR], 1.5 [1.3–3.2]; P =0.01 and HR, 2.3 [1.8–2.8]; P =0.001) and a higher cardiac mortality (HR, 1.3 [1.1–2.1]; P =0.01 and HR, 1.7 [1.3–2.5]; P =0.002). After 1 month, the sPAP decreased ≥15 mm Hg in 32% and 35% of the patients in groups 2 and 3. Baseline sPAP >60 mm Hg (HR, 1.6 [1.1–2.3]; P =0.03) and, in a larger extent, a persistent severe PH after 1 month (HR, 2.4 [1.5–2.8]; P =0.004), independently predicted 1-year mortality, whereas the 1-month reduction of the sPAP did not. Conclusions—: The persistence of severe PH after transcatheter aortic valve replacement is a stronger predictor of 1-year mortality than baseline severe PH. The early reduction of sPAP is not associated with a reduced mortality. The benefit of transcatheter aortic valve replacement in terms of quality of life is substantial in patients with and without a reduction of sPAP at early follow-up. Abstract : Supplemental Digital Content is available in the text.